2019
DOI: 10.1038/s41598-019-40161-0
|View full text |Cite
|
Sign up to set email alerts
|

The different influences of drought stress at the flowering stage on rice physiological traits, grain yield, and quality

Abstract: Seasonal drought is a major threat to rice production. However, the sensitivity of rice to drought stress (DS) at different growth periods remains unclear. The objective of this study was to reveal the different impacts of DS at the flowering stage on rice physiological traits, grain yield, and quality. Field experiments were conducted with two rice cultivars, Yangliangyou 6 (YLY6) and Hanyou 113 (HY113) under two water treatments (traditional flooding (CK) and DS at flowering stage) in 2013 and 2014. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
136
2
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(157 citation statements)
references
References 64 publications
14
136
2
5
Order By: Relevance
“…Severe drought stress during reproductive stage of rice accounted for economic losses of 48 to 94% (Kim et al 2020). Furthermore, it also resulted in poor quality and aroma of rice grains (Arsa et al 2017;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Severe drought stress during reproductive stage of rice accounted for economic losses of 48 to 94% (Kim et al 2020). Furthermore, it also resulted in poor quality and aroma of rice grains (Arsa et al 2017;Yang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Submergence of rice plants for one to two weeks due to flash flooding is another major constraint prevailing mainly in rainfed lowlands [19]. The long duration cultivars usually come across with flooding at early stages followed by drought during flowering, resulting in huge yield losses [20]. Similarly, salinity which is characterized by high concentration of soluble salts is another widespread soil problem next only to drought and acts as a serious limitation for rice production worldwide [21].…”
Section: Major Abiotic Stresses In Ricementioning
confidence: 99%
“…Water deficit could occur at any time from booting to mature stage, and the intensity of stress depends on the duration of water-deficit 7 . However, the sensitivity to water deficit shows significant difference at different growth period of rice, many previous studies have shown that reproductive stage is the most susceptible period for rice [8][9] . The physiological activity and metabolism of rice flag 72 leaves were significantly reduced under drought stress at heading stage, which resulted 73 in a conspicuous decrease in dry matter accumulation.…”
Section: Introduction 57mentioning
confidence: 98%